2016
DOI: 10.1007/s00203-016-1313-6
|View full text |Cite
|
Sign up to set email alerts
|

Acyl homoserine lactone-based quorum sensing stimulates biofilm formation by Salmonella Enteritidis in anaerobic conditions

Abstract: Quorum sensing regulates a variety of phenotypes in bacteria including the production of virulence factors. Salmonella spp. have quorum sensing systems mediated by three autoinducers (AI-1, AI-2, and AI-3). The AI-1-mediated system is incomplete in that the bacterium relies on the synthesis of signaling molecules by other microorganisms. This study aimed to evaluate the influence of the AI-1 N-dodecanoyl-DL-homoserine lactone (C12-HSL) on the growth, motility, adhesion, and biofilm formation of Salmonella ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…These results highlight the importance of good hygiene and disinfection practices in dairy equipment such as bulk tanks. Quorum-sensing molecules can increase biofilm formation in Salmonella , and this cell mechanism could play an important role for bacterial communication in multispecies biofilms [ 32 , 33 ]. Due to the microbiota composition of raw milk, Salmonella cells can integrate in biofilms formed by other bacterial genera as a response to quorum-sensing molecules produced by other microorganisms and liberated to the milk.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the importance of good hygiene and disinfection practices in dairy equipment such as bulk tanks. Quorum-sensing molecules can increase biofilm formation in Salmonella , and this cell mechanism could play an important role for bacterial communication in multispecies biofilms [ 32 , 33 ]. Due to the microbiota composition of raw milk, Salmonella cells can integrate in biofilms formed by other bacterial genera as a response to quorum-sensing molecules produced by other microorganisms and liberated to the milk.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculum was prepared according to Almeida et al [ 35 , 41 ]. Tryptone soy broth (TSB; Sigma-Aldrich, India) was prepared with CO 2 under O 2 -free conditions, dispensed in anaerobic bottles that were sealed with butyl rubber stoppers and then autoclaved (anaerobic TSB).…”
Section: Methodsmentioning
confidence: 99%
“…enterica serovar Typhi containing plasmid pRST98, which harbors the virulence gene rck , increased adhesion to HeLa cells after 1 h at 37 °C in the presence of 5% CO 2 gas [ 40 ]. Biofilm formation by Salmonella Enteritidis PT4 578 in polystyrene surface was positively regulated by C12-HSL after 36 h in anaerobiosis, even though no growth changes were observed in planktonic cells [ 34 , 41 ]. Similarly, Bai and Rai [ 42 ] showed that biofilm formation on polystyrene was increased by Salmonella Typhimurium when cultivated with N -butyryl homoserine lactone (C4-HSL) e C6-HSL.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of C12-HSL was based on studies showing its increased effect on biofilm formation by Salmonella compared to other AHLs with shorter carbon chains due to its higher affinity to SdiA. The concentration too was based on those same studies ( Campos-Galvão et al, 2015 , 2016 ; Almeida et al, 2016 , 2017b , 2018 ). The acetonitrile concentration was less than 1% (vol/vol) in the culture medium since according to Michael et al (2001) , this concentration does not exhibit an effect on the growth and response of Salmonella to AHL.…”
Section: Methodsmentioning
confidence: 99%
“…This could be explained by its higher binding affinity to the SdiA protein when compared to other AHLs through molecular docking studies ( Almeida et al, 2016 ). Besides C12-HSL, other AHLs tested did not influence the growth of Salmonella Enteritidis PT4 578 cultivated in anaerobic Tryptic Soy Broth (TSB) medium at 37°C ( Campos-Galvão et al, 2015 ; Almeida et al, 2017b ). Cultivation of Salmonella Enteritidis PT4 578 in anaerobic TSB medium supplemented with C12-HSL also led to alterations in protein abundance and levels of organic acids associated with the early stationary phase of growth ( Almeida et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%